2019
DOI: 10.1186/s12887-019-1721-2
|View full text |Cite
|
Sign up to set email alerts
|

Nasal continuous positive airway pressure with head cap fixation as a contributing factor to extensive scalp necrosis in a preterm neonate with early-onset sepsis and scalp hematoma

Abstract: BackgroundNasal continuous positive airway pressure (CPAP) is widely used in the treatment and prevention of respiratory distress in preterm neonates, with only few severe adverse skin effects reported.Case presentationA preterm neonate was born at 34 + 1 weeks of gestation, birth weight 1860 g, and presented with early-onset sepsis (EOS) and scalp hematoma. He developed respiratory distress day 2 after birth. Antibiotics, nasal CPAP and other supportive treatment were initiated. A scalp hematoma in the occipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
0
0
Order By: Relevance
“…This research shows that: skin damage rate of nasolabial sulcus, septum in children with new nasal fixation is only 5.66 % and 9.43 %, while the skin injury rates of nasolabial sulcus and nasal septum in children with traditional nasal fixation were as high as 24.52 % and 28.30 %. It is suggested that the use of new nasal fixation of appropriate type of equipment, appropriate hat and hydrocolloid dressing in continuous positive airway pressure (CPAP) can significantly reduce the skin damage in the nasolabial groove and nasal septum and improve the family members of newborns satisfaction with nursing services at the same time, which is consistent with existing studies [13][14][15] . In conclusion, in neonates receiving continuous positive airway pressure (CPAP) through the nose, the hydrocolloid dressing is cut into a bunny shape and perforated according to the size of the child's nostril, then attached to the child's nose with a new type of nasal fixation The method can significantly reduce the damage of the nasolabial fold and septum skin and improve the quality of care and the satisfaction of the children's family with the nursing service.…”
supporting
confidence: 76%
“…This research shows that: skin damage rate of nasolabial sulcus, septum in children with new nasal fixation is only 5.66 % and 9.43 %, while the skin injury rates of nasolabial sulcus and nasal septum in children with traditional nasal fixation were as high as 24.52 % and 28.30 %. It is suggested that the use of new nasal fixation of appropriate type of equipment, appropriate hat and hydrocolloid dressing in continuous positive airway pressure (CPAP) can significantly reduce the skin damage in the nasolabial groove and nasal septum and improve the family members of newborns satisfaction with nursing services at the same time, which is consistent with existing studies [13][14][15] . In conclusion, in neonates receiving continuous positive airway pressure (CPAP) through the nose, the hydrocolloid dressing is cut into a bunny shape and perforated according to the size of the child's nostril, then attached to the child's nose with a new type of nasal fixation The method can significantly reduce the damage of the nasolabial fold and septum skin and improve the quality of care and the satisfaction of the children's family with the nursing service.…”
supporting
confidence: 76%
“…(17) Uma pesquisa realizada com neonatos observou 410 cateteres centrais de inserção periférica (PICC) onde 47 (11,4%) apresentavam flebite química e 231 (56,3%) disfunção mecânica. (18) Os autores (19) registraram uma lesão extensa em um prematuro, hematoma no couro cabeludo, na região occipital que complicou pela pressão na tampa do CPAP nasal, ocasionando uma necrose extensa do couro cabeludo igual a 6% da superfície corporal total, sendo necessário realizar desbridamento e enxerto (19) . A pesquisa dos autores (20) observaram a ocorrência de queimaduras de laringoscópio durante a intubação neonatal, ocasionada pelo aumento da temperatura das lâmpadas, calor significativo para causar lesão térmica na pele neonatal.…”
Section: Métodounclassified